Factors affecting the practice of islamic professional ethics : A case study of a public sector - Mat, Zawiah; Basir, Siti Arni; Jano, Zanariah (Medwell Publishing, 2016)
This study aimed to identify and analyse factors which affected practice of Islamic Professional Ethics (IPE) in the management of a public sector in Malaysia. This study employed a quantitative method through a survey using questionnaires which were distributed to a total of 198 managerial and professional employees in the Royal Malaysian Customs Department. The findings yielded nine significant factors which influenced IPE and the four most prominent were religious appreciation, teamwork, leadership and attitude which were the core elements towards sustainable IPE practice. Other five factors which scored highly were regulation, training, environment, motivation and public complaint. This study helps in bridging the gaps in literature on ethics professionalism Islam in organizations and assists managers in implementing IPE